2010
DOI: 10.1007/s10646-010-0582-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequential effects of cadmium on genotoxicity and lipoperoxidation in Vicia faba roots

Abstract: Kinetics of stress responses to Cd exposure (50, 100 and 200 μM) expanding from 12 to 48 h were studied in roots of hydroponically cultivated-Vicia faba seedlings. The heavy metal induced toxicity symptoms and growth arrest of Vicia roots gradually to the Cd concentration and duration of the treatment. The intracellular oxidative stress was evaluated with the H(2)O(2) production. The H(2)O(2) content increased gradually with the sequestered Cd and root growth inhibition. Lipid peroxidation-evidenced by malondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
(42 reference statements)
0
19
0
1
Order By: Relevance
“…Disturbance of the function of the spindle of cell division is probably caused by the ability of cadmium ions to bind to sulfhydril groups of tubulin where cysteine groups actively participate in the regulation of dynamics of microtubules' assembly [25]. This assumption is corroborated by the data about extension of relative duration of prophases and metaphases under the effect of cadmium acetate and reduction in the level of anaphases and telophases (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Disturbance of the function of the spindle of cell division is probably caused by the ability of cadmium ions to bind to sulfhydril groups of tubulin where cysteine groups actively participate in the regulation of dynamics of microtubules' assembly [25]. This assumption is corroborated by the data about extension of relative duration of prophases and metaphases under the effect of cadmium acetate and reduction in the level of anaphases and telophases (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The significant difference of the micronuclei frequency between the control and cells exposed to NaCl indicates the sensitivity and the reliability of this test system. Such sensitivity of V. faba roots was also caused by a wide range of other stress conditions such as heavy metal treatments (Souguir et al, 2008(Souguir et al, , 2011Yi et al, 2010), olive mill waste water (El Hajjouji et al, 2007), pesticides (Sta et al, 2012), and diesel exhaust particulate matter (Corrˆea et al, 2016). Recently, an interlaboratory study of seven laboratories from three countries, investigating the robustness of this test for soil or soil materials assessment, confirmed its applicability based on the international ISO 29200 protocol (Cotelle et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies reported that the cell division during growth was widely affected by several stress conditions (Firbas and Amon, 2013;Mekki, 2014;Souguir et al, 2011). Under salt stress (40-160 mM), decreases in mitotic index inducing growth inhibition were also investigated in Allium cepa roots (Teerarak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic oral Cd ingestion can cause the itai-itai disease that is the most severe form of chronic Cd poisoning, and Cd has been classified as a carcinogen by the International Agency for Research on Cancer (IARC) (Takaki et al 2004;Bertin and Averbeck 2006). Cd can also induce oxidative stress and leads to cell death depending on the exposure time due to the increase of reactive oxygen species in cells (Souguir et al 2011;Benavides et al 2005;Company et al 2004). Therefore, it is necessary to assess the toxicological effects in the intertidal organisms induced by Cd using the biomarkers.…”
Section: Introductionmentioning
confidence: 99%